Circulating Tumor Cell Detection for Therapeutic and Prognostic Roles in Breast Cancer - Saiying Ma; Xiaojia Wang; Peter Ping Lin; Lei Lei (Cancer Medicine)
ABSTRACT Background Circulating tumor cells (CTCs) are pivotal liquid biopsy (LB) biomarkers for breast cancer (BC), offering non‐invasive insights into tumor progression and metastasis. Despite their clinical promise, CTC detection remains technically challenging due to their extreme rarity in peripheral blood. Methods This review systematically evaluates CTC detection methodologies, including immunoaffinity‐based approaches and biophysical techniques, which exhibit inherent trade‐offs in sensitivity, specificity, and compatibility with downstream analyses. Furthermore, post‐isolation molecular characterization methods spanning genomic, transcriptomic, and proteomic analyses are also critically assessed. Key Findings CTC molecular profiling holds significant clinical relevance, enabling early diagnosis, prognostic stratification, and real‐time monitoring of therapeutic response. Baseline CTC counts or quantitative/phenotypic changes during treatment inform therapeutic decision‐making, predict drug resistance, and correlate with recurrence risk and metastatic progression. Conclusion Multimodal analysis integrating CTC morphology, surface markers, and molecular alterations advances precision therapy. However, standardization of detection platforms and clinical validation of CTC‐guided protocols remain essential.